Moderating effect of differences in coaches' cultural backgrounds: the relationship between the coaches' leadership style and the athletes' satisfaction / Mohd Hardi Razali, Wirdati Md. Radzi and Solha Husin - Razali, Mohd Hardi; Md. Radzi, Wirdati; Husin, Solha (Universiti Teknologi MARA, 2020)
This study examined the moderating effect of local and foreign coaches in the relationship between the coaches' leadership styles and the athletes' satisfaction in a case of high performance athletes in Malaysia. The population of the study were the athletes under the organization of Majlis Sukan Negara who were selected using purposive sampling technique (N = 350). Leadership Scale for Sports (LSS) (Chelladurai & Salleh, 1980) and Athlete Satisfaction Questionnaire (ASQ) (Chelladurai & Reimer, 1997) were the survey tools for this research. The five domains of leadership style showed positive correlation with the athletes' satisfaction levels (p < .05); Training and instruction, r = 0.623, Democratic, r = 0.500, Autocratic, r = 0.126, Social support, r = 0.540 and Positive feedback, r = 0.490. There is a significant difference between autocratic leadership style and gender (p < .05) Females perceived coaches' autocratic leadership style higher than male. However, in the athletes' satisfaction, there is no significant difference between genders (p > .05). In comparing the age groups, there is a significant difference in training and instruction leadership style and athletes; with the satisfaction level of p < .05. The age group of 24 - 26 years old perceived training and instruction, and the athletes' satisfaction greater among all age groups. The lowest athletes' satisfaction was for the group of 18 - 20 years old. Based on the coaches' nationality, training and instruction, and the athletes' satisfaction also show significant difference (p < .05). Foreign coaches exhibited greater training and instruction style than the locals. On the other hand, the athletes are highly satisfied of the local coaches compared to the foreign coaches. The significant correlations were observed between all leadership styles domains and the athletes' satisfaction (p < .05) except for 'autocratic style' in both local and foreign coaches. This study was expected to extend the knowledge of leadership in sport, where the cultural differences have never been investigated as the moderating effect in the relationship between the coaches' leadership styles and athletes' satisfaction levels, and to improve the quality of coaching by the recommended appropriate strategies in controlling the effects of cultural differences.